DEFINITION AND CLASSIFICATION OF ANADIPLOSIS IN LINGUISTIC STUDIES (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article examines anadiplosis as a rhetorical and stylistic device in linguistic studies, tracing its etymology, historical development, and contemporary classifications. Originating from Ancient Greek, anadiplosis refers to the repetition of the final word or phrase of one clause at the beginning of the following unit, creating semantic and structural continuity. The research explores the typological framework of anadiplosis, categorizing it into grammatical, lexical, and semantic varieties, each with distinct subtypes that operate at different linguistic levels. The article also distinguishes anadiplosis from related stylistic devices such as anaphora, epiphora, symploce, epanalepsis, polyptoton, and gradatio, highlighting its unique end-beginning pattern. By synthesizing classical rhetorical traditions with modern linguistic approaches, this study contributes to a comprehensive understanding of anadiplosis as both a formal textual mechanism and a cognitive-semantic tool that enhances cohesion, emphasis, and persuasive power in various discourse types.